Community Development Initiatives Implementation and Disaster Risk Management Practices in Calamba City Barangays - Aguila, Jose Roderick (Social Sciences and Development Review, 2025)
This study examined the relationship between community development frameworks and disaster risk management (DRM) practices using a quantitative descriptive correlational design. Data were gathered from 150 respondents, 40 barangay officials, and 110 community members from Barangays Palingon, Lingga, and Sampiruhan in Calamba City through a validated researcher-made survey (CVR = 1.00) utilizing a four-point Likert scale. Statistical analyses included a paired T-test (.05 significance level) and Pearson Product-Moment Correlation.Findings indicated that community development initiatives and DRM practices were generally "Fully Implemented" and "Fully Manifested," with Self-Understanding (3.49) and Preparedness (3.62) receiving the highest ratings, while Engage and Empower, Reflect and Celebrate (3.35), and Recovery (3.46) were the lowest. Significant differences were observed in Preparedness (p = 0.001) and Reflect and Celebrate (p = 0.044), while Self-Understanding (p = 0.175) showed no significant difference.Correlation analysis revealed significant relationships, with Engage and Response (p = 0.001) as the strongest and Reflect and Preparedness (p = 0.026) as the weakest, while no significant relationship was found in Reflect and Mitigation (p = 0.877). To enhance disaster preparedness and response, an action plan was proposed to equip barangay officials with hands-on training in Incident Command System (ICS) Level 1.
Keywords: Community development, community frameworks, disaster risk management, initiatives implementation.